An innovative concept map approach for improving students' learning performance with an instant feedback mechanism - Wu, Po-Han; Hwang, Gwo-Jen; Milrad, Marcelo; Ke, Hui-Ru; Huang, Yueh-Min (British journal of educational technology, 2012)
Concept maps have been widely employed for helping students organise their knowledge as well as evaluating their knowledge structures in a wide range of subject matters. Although researchers have recognised concept maps as being an important educational tool, past experiences have also revealed the difficulty of evaluating the correctness of a concept map. It usually takes days or weeks for teachers to manually evaluate the concept maps developed by students; consequently, the students cannot receive timely feedback from the teachers, which not only affects their learning schedules, but also significantly influences the students' learning achievements. In this paper, a computer‐based concept map‐oriented learning strategy with real‐time assessment and feedback is proposed in order to cope with the problems mentioned above. Our approach provides immediate evaluation of concept maps and gives also real‐time feedback to the students. An experiment has been conducted to evaluate the effectiveness of this new strategy in comparison with the conventional computer‐based concept map approach. It is found that our innovative approach can be significantly beneficial to promote learning achievements as well as the learning attitudes of students.